Study on Application of Hardware Efficient CIC Compensation Filter in Narrow Band Filtering - Awasthi, Vishal; Raj, Krishna (Novel Perspectives of Engineering Research Vol. 2, 2021)
In many communication and signal processing systems, it is highly desirable to implement an efficient narrow-band filter that decimate or interpolate the incoming signals. This paper presents hardware efficient compensated CIC filter over a narrow band frequency that increases the speed of down sampling by using multiplierless decimation filters with polyphase FIR filter structure. FIR filter is one of the fundamental processing elements in any signal processing system. The proposed work analyzed the performance of compensated CIC filter on the bases of the improvement of frequency response with reduced hardware complexity in terms of no. of adders and multipliers and produces the filtered results without any alterations. CIC compensator filter demonstrated that by using compensation with CIC filter improve the frequency response in passed of interest 26.57 % with the reduction in hardware complexity 12.25% multiplications per input sample (MPIS) and 23.4% additions per input sample (APIS) w.r.t. FIR filter respectively.